Confronting our freedom leading a culture of chosen accountability and belonging - Block, Peter; Koestenbaum, Peter 1928- (Hoboken, New Jersey John Wiley & Sons, 2023)
"Confronting Our Freedom is about reframing the common practices rising from traditional thinking about management and leadership. Most management theory and practice are about the need for clear constraints to succeed in the world where we work, but this now conventional thinking about managing calls for adaptation when working remotely has become common. This book is an invitation to freedom. Structuring our world for freedom is the path to collective accountability. It is ultimately a friendly look into how we might reimagine our participation in the working world, analyzing the strategy, execution, and management of philosophers, leaders, and educators"-- Provided by publisher.
Includes index.
Keywords: Leadership; Management -- Philosophy